Meningkatkan Rasa Kepedulian Anak Usia Dini Melalui Kegiatan Infaq Sedekah Di Tk Khas Al-Amin Bongkor - Sofiah, Sofi Siti; Widiyastuti , Arie; Hatiningsih , Nurligar (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
SOFI SITI SOFIAH: Increasing the Sense of Caring for Early Childhood Through Alms Infaq Activities at Kindergarten Khas Al-Amin Bongkor. This research aims to find out how to increase the sense of caring for young children through alms infaq activities at Kindergarten Khas Al- Amin Bongkor. The study was carried out utilizing Kemmis and McTaggart's classroom action research methodology. Two cycles are used to describe the acts, with each cycle having four stages: preparation, action, observation, and reflection. A cycle lasts for two days. Early childhood concern increased by 80 percent from the pre-cycle to the second cycle as a consequence of this classroom action investigation. The data was assessed both statistically and subjectively based on the study of the quantitative data. Qualitatively, the habituation system involves activities in the form of learning while playing with loose part media provided by the school and coins or paper that children bring from home as snacks for school, but the money is not used for snacks, but rather for alms savings. which aims to improve children's habit of not eating out during class lessons. So the school makes rules for all students so that parents do not get into the habit of giving their children to school with pocket money, but rather with food directly from home. Apart from this method, educators also apply the habit of learning while playing through the beautiful activities of sharing and caring for friends who need help, as well as caring for the surrounding environment, in order for them to be able to demonstrate their compassionate attitude through empathy and for instructors to recognize and reward students who choose to do so an attitude of caring about positive things.